2022
DOI: 10.1091/mbc.e21-10-0532
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence of anaphase spindle mechanics in nematode embryos constrained by antagonistic pulling and viscous forces

Abstract: Cellular functions like cell division are remarkably conserved across phyla. However the evolutionary principles of cellular organization that drive it are less well explored. Thus, an essential question remains: to what extent cellular parameters evolve without altering the basic function they sustain? Here we have observed 6 different nematode species for which the mitotic spindle is positioned asymmetrically during the first embryonic division. Whereas the C. elegans spindle undergoes oscillations during it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…For this, we microinjected passive beads and Next, we used the mean diffusion coefficient of the beads estimated from ensemble-averaged MSDs to calculate cytoplasmic viscosity using the Stokes-Einstein equation and found that 2-cell embryos have a cytoplasmic viscosity of 3.6 Pa.S (Fig 5I). This is broadly consistent with the viscosity reported for C. elegans and Drosophila embryos (0.67-1 Pa.S), mouse and human fibroblasts (1-4.5 Pa.S) derived using similar intracellular measurements (Kole et al, 2004;Daniels et al, 2006Daniels et al, , 2010Wessel et al, 2015;Khatri et al, 2022). Notably, we found that the cytoplasmic viscosity of mouse oocytes was 0.5 Pa.S, over 7 times lower than in 2-cell embryos.…”
Section: -Cell Embryos Exhibit High Cytoplasmic Viscosity and Do Not ...supporting
confidence: 91%
See 1 more Smart Citation
“…For this, we microinjected passive beads and Next, we used the mean diffusion coefficient of the beads estimated from ensemble-averaged MSDs to calculate cytoplasmic viscosity using the Stokes-Einstein equation and found that 2-cell embryos have a cytoplasmic viscosity of 3.6 Pa.S (Fig 5I). This is broadly consistent with the viscosity reported for C. elegans and Drosophila embryos (0.67-1 Pa.S), mouse and human fibroblasts (1-4.5 Pa.S) derived using similar intracellular measurements (Kole et al, 2004;Daniels et al, 2006Daniels et al, , 2010Wessel et al, 2015;Khatri et al, 2022). Notably, we found that the cytoplasmic viscosity of mouse oocytes was 0.5 Pa.S, over 7 times lower than in 2-cell embryos.…”
Section: -Cell Embryos Exhibit High Cytoplasmic Viscosity and Do Not ...supporting
confidence: 91%
“…Unlike oocytes which use a non‐specific, diffusion‐based nuclear centring mechanism based on actin vesicles, we found that 2‐cell embryos employ a nucleus‐targeted and actin‐dependent mechanism involving the motor myosin II rather than myosin Vb. Intracellular microrheology measurements suggest that mouse 2‐cell embryos exhibit higher cytoplasmic viscosity than mouse oocytes and other cell types (Kole et al , 2004; Daniels et al , 2006; Wessel et al , 2015; Khatri et al , 2022). Since myosin Vb has been proposed to fluidise the oocyte cytoplasm (Ahmed et al , 2018), it is possible that its inactivity in 2‐cell embryos contributes to a more viscous cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…The simplest hypothesis is that maternal and paternal cytoplasm might not mix during the 45 min from GVBD to pronucleus formation due to the high viscosity of cytoplasm. Attempts at measuring cytoplasmic viscosity of the C. elegans zygote have revealed values from 0.67 – 1.0 Pa s (3234) which are similar to the viscosity of 100% glycerol. Alternatively, the sperm contents might be held together by a cytoskeleton-like matrix as proposed for the Balbiani body (35).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually a cytokinetic furrow is formed, which divides the cytoplasm, giving rise to two asymmetric daughter cells. The cytoplasm fluid mechanical properties have been characterized to result in an effective viscosity ranging between 0.6 to 1 Pa-s based on either microrheology of tracking passive yolk granule movement [6, 9, 10], single particle tracking of injected fluorescent sub-micron particles [11] and spindle displacement and recoil using magnetic tweezers [12]. AAcross-speciesross-species, some closer and some evolutionarily more distant to C. elegans have demonstrated spindle movements in Anaphase vary with very little correlation to phylogenetic distance [13].…”
Section: Introductionmentioning
confidence: 99%
“…AAcross-speciesross-species, some closer and some evolutionarily more distant to C. elegans have demonstrated spindle movements in Anaphase vary with very little correlation to phylogenetic distance [13]. In contrast the mechanics of the cortical pulling force (F) acting on the spindle, effective cytoplasmic viscosity ( η eff ) and embryo size ( L ) when combined as ω = F/ ( L· η eff ) is predictive of spindle oscillation onset [10]. Comparative studies on spindle dynamics have revealed universal scaling relationships between embryo size and spindle dynamics in C. elegans strains alone [14].…”
Section: Introductionmentioning
confidence: 99%